THE ROLE OF LOCAL SELF-GOVERNMENT IN THE POLISH CONSTITUTIONAL SYSTEM - Jakubek-Lalik, Jowanka (Zbornik radova Pravnog fakulteta u Nišu, 2020)
Local government reform has been acknowledged to be one of the biggest successes of political transformation in Poland. Municipalities (gminy) gained strong powers and are now responsible for many public services of crucial importance to local communities. The districts (powiaty) and provinces (województwa) were also given important competences in the fields of public services and the responsibility for their development. Their autonomy is guarded by legal, institutional and financial guarantees and strong local leaders. Carefully designed institutional framework of local and regional government seemed to be permanent and durable, guaranteeing strong decentralization and providing local and provincial authorities with substantial decision-making powers and responsibilities for vast majority of public services.Such a broad field for the functioning of the local government does not remain without interpretation problems. The consecutive central governments were finding common ground in their instrumental approach to local authorities’ independence. It was convenient for the state to decentralize problems and challenges, while keeping control over finance and other resources, as well as looking for ways to increase supervisory powers over local government. Almost 30 years after reintroduction of territorial self-government in Poland, it is expected to be well rooted in the constitutional system of Poland - but is it really so?
Keywords: пољски уставни систем; локална и регионална самоуправа